Sustainable Food Consumption Practices: Insights into Consumer Experience - Migliore, Giuseppina (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
In recent years, the increasing consumer concern towards food safety, environmental sustainability and social justice issues have stimulated new consumption practices more oriented towards social, economic and environmental sustainability. These include the growing consumers' preferences towards organic food, local food, and other sustainable foods and beverages consumption, as well as the spread of alternative distribution chains, which emphasize the short-distance transportation of food and the direct relationship between consumers and producers. In addition, these sustainable consumption practices seem also to involve tourist destination choices, rural tourism and gastronomy interest. This Special Issue aims to contribute to the literature on sustainable consumption practices by enriching discussions on consumers experiences and by emphasizing the motivational and demographic factors as well as the cultural and situational factors that guide consumer behaviour towards these practices.